Sirt1-Overexpressing Mesenchymal Stem Cells Drive the Anti-tumor Effect through Their Pro-inflammatory Capacity - Ye, Fei (Mol Ther, 2020)
The major obstacles for the efficacy of tumor immunotherapies are their immune-related systemic adverse events. Therefore, tumor tropism property and pro-inflammatory ability of mesenchymal stem cells (MSCs) could be utilized in combination to potentiate local immunity for cancer eradication. We previously observed that MSCs with the type III histone deacetylase silent information regulator 2 homologue 1 (Sirt1) overexpression displayed a pro-inflammatory capacity. However, the anti-tumor effect of Sirt1-overexpressing MSCs and the role of Sirt1 in regulating the pro-inflammatory capacity of MSCs still need to be clarified. In this study, utilizing the hepatic metastasis model of colorectal carcinoma, we demonstrated that Sirt1-overexpressing MSCs significantly exerted anti-tumor activity through increasing the number of CD8(+) T cells. Furthermore, Sirt1 did not affect chemokine secretion in MSCs induced by inflammatory cytokines, but impaired the immunosuppressive ability of MSCs through suppressing inflammatory cytokine-stimulated inducible nitric oxide synthase (iNOS) production via deacetylating p65. iNOS overexpression negated the anti-tumor effect of Sirt1-overexpressing MSCs. Collectively, our data defined Sirt1 as the critical regulator for modulating the pro-inflammatory ability of MSCs, and they suggested that Sirt1-overexpressing MSCs secreting chemokines but little iNOS under the inflammatory milieu were capable of attracting immune cells to close proximity without suppressing their proliferation, thereby achieving a potent anti-tumor effect.